Measuring the Impact of the Happiness of Faculty Members on Academic Performance - Chopra, Alka; Jain, Trilok Kumar (Journal of Advanced Research in English & Education; Vol 9 No 1 (2024): Journal of Advanced Research in English & Education, 2024)
Happiness refers to a sense of satisfaction and contentment. This quality has contributed to the overall productivity of people. This quality is equally important among the teaching fraternity. This paper seeks to study the impact of happiness on the performance of teachers. The findings suggest that happiness can be increased by providing greater autonomy, freedom, and opportunities to experiment.